Analisis Perbandingan Metode Full Costing Dan Variabel Costing Dalam Penentuan Harga Pokok Produksi Dan Harga Jual Pada UMKM Rcroastery.Id Di Kabupaten Bandung - Melani Melani; Giatri Divianis; Dadang Husen Sobana; Rima Hikmatul Karimah (STIE Amkop Makassar, 2025)
This study analyzes the calculation of the cost of goods manufactured (COGM) using full costing and variable costing methods, focusing on their implications for pricing and profits at RCRoastery.id in Bandung District. A qualitative descriptive approach is used, with data collected through observation, interviews, and documentation. The analysis reveals that the full costing method results in a total COGM of IDR 40,200,000, a unit cost of IDR 114,857, and a selling price of IDR 183,771. In contrast, the variable costing method produces a total COGM of IDR 39,950,000, a unit cost of IDR 114,142, and a selling price of IDR 182,528. The IDR 250,000 difference in COGM is due to fixed cost allocation in full costing. The full costing method yields a net profit of IDR 23,009,468, while the variable costing method generates IDR 15,291,468. These findings suggest that full costing provides a comprehensive view of production costs, while variable costing is better for competitive pricing. The study recommends MSMEs choose a method aligned with strategic goals: full costing for holistic cost management and variable costing for efficiency and market competitiveness.